1970
DOI: 10.1002/hlca.19700530704
|View full text |Cite
|
Sign up to set email alerts
|

Die Struktur von Panepoxydon und verwandten Pilzmetaboliten

Abstract: in 50 ml Aceton wurden mit 0,3 ml 3~ Salzsaure 4 Std. untcr Ruckfluss gekocht. Das Losungsmittel wurde im Vakuum weitgehend abgedampft. Nach Zusatz von Natriumhydrogencarbonat extrahierte man mit Chloroform. Der Chloroformauszug wurde ahgedampft und der Ruckstand mit Chloroform/Methanol = 5/1 dunnschichtchromatographisch gereinigt. Ausheute : 10 mg, die nicht kristallisierten, aher sich in allen anderen untersuchten Eigenschaften als identisch mit der in Versuch 13.1. beschriebenen Base erwiesen (UV.-, 1R.-, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Hypnophilin (4) (Kis et al 1970), while panepoxydone was isolated with hypnophilin from cultures of the L. connatus (Rukachaisirikul et al 2005) and L. crinitus (Erkel et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypnophilin (4) (Kis et al 1970), while panepoxydone was isolated with hypnophilin from cultures of the L. connatus (Rukachaisirikul et al 2005) and L. crinitus (Erkel et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrohypnophilin (3) was isolated from a culture of L. crinitus (Abate & Abraham 1994) and L. conatus (Rukachaisirikul et al 2005). Panepoxydone and neopanepoxydol were obtained from fermentations of Panus rudis and Panus conchatus (Kis et al 1970), while panepoxydone was isolated with hypnophilin from cultures of the L. connatus (Rukachaisirikul et al 2005) and L. crinitus (Erkel et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The modifications are manifested in oxygenation, unsaturation, degradation or rearrangement to form different ring skeletons. In our efforts to discover new natural products from Thai Basidiomycota, 9 we report in this paper on the isolation, structure determination and the biological evaluation of novel hirsutane compounds with unprecedented modification named lentinulactam (1), along with four known compounds, connatusin A (2), 8 connatusin B (3), 8 6-hydroxy-2,2-dimethylchroman-4-one (4), 10 and 6-methoxy-2,2-dimethylchroman-4-ol (5) 11 from the basidiomycete Lentinus cf. fasciatus collected in Thailand.…”
mentioning
confidence: 99%
“…12,13 Our findings supported the previously reported configuration for connatusins and confirmed that lentinulactam (1) Compounds 4 and 5 were assigned as 6-hydroxy-2,2-dimethylchroman-4-one (4), and 6-methoxy-2,2-dimethylchroman-4-ol (5) (Figure 1) by comparison of their HRESIMS and NMR data with those in the literature. 10,11 The nomenclature of compound 5 was incorrectly published by Rukachaisirikul et al 8 as 2,2-dimethyl-3-hydroxy-6-methoxy-4-chromanone. The correct nomenclature is 6-methoxy-2,2-dimethylchroman-4-ol.…”
mentioning
confidence: 99%
See 1 more Smart Citation